Mental Arithmetic Ability and its Relationship to Working Visual Memory among Primary School Pupils (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study sheds the light on determining the correlation between mental arithmeticability and working visual memory, and the sample of the study members consisted of368 male and female pupils from private schools affiliated to the General Directorateof Education in Babylon In order to achieve the objectives of the current research, itwas necessary to have a test to measure mental arithmetic for primary school pupils,and given the absence of a local or Arabic test within the limits of the researcher’sknowledge, she decided to prepare a test in mental arithmetic consisting of five parts,four of which are related to numerical issues and a special part to verbal issues and todefine the concept of arithmetic The researcher adopted the Reys 1993 study (Reys,1993). Where the first part consists of the skill of addition and contains fourparagraphs, the second part is related to the skill of subtraction and contains fourparagraphs, the third part is related to the skill of multiplication and contains fiveparagraphs, the fourth part is concerned with the skill of division and contains fiveparagraphs, as for the fifth part, this part is specific to verbal skills and contains It isdivided into four paragraphs distributed over the four arithmetic operations (addition,subtraction, multiplication, division), and thus the test paragraphs are (22) items. Asfor the working visual memory test. The test consists of (40) paragraphs in its finalform, where the paragraphs are in the form of optical slides, and the first slides beginwith two components in each slide, then gradually progress until they become (5-6)components. All are simple black and white shapes. The test can be appliedindividually or collectively, and in the case of applying the test in an individual way,it is possible to display the test on a computer and statistical analysis of the two testparagraphs was conducted and conclusions were reached on the basis of which a setof proposals and recommendations were developed